EVALUATION OF QUALITY PARAMETERS IN COTTON PRODUCTION (Gossypium hirsutum L.) UNDER WATER STRESS CONDITIONS - Özlem AVŞAR; Emine KARADEMİR (Journal of Applied Life Sciences and Environment)
Decreasing water availability for cotton production has compelled researchers to engage in studies about rising water use efficiency by improving water management. The impacts of different irrigation levels on the fibre qualities of drip-irrigated cotton were evaluated in Diyarbakır, Southeast Anatolia Region of Turkiye. Three cotton varieties, ‘Stoneville 468’ (ST 468), ‘FiberMax 832’ (FM 832), and ‘Kartanesi’, and three levels of irrigation were tested in 2017 and 2018. Treatments were I 50 (50% water stress), I 75 (25% water stress), and the fully irrigated treatment I 100, which was obtained from Class-A pan evaporation. According to the two-year results of the study, water stress caused a decline in fineness, length, strength, elongation, uniformity ratio, and spinning consistency index (SCI) values of fibre, while fibre yellowness and short fibre ratio values increased. Fibre brightness was not affected by water stress. There were significant differences among varieties concerning quality parameters. FM 832 has come to the fore with regard to fibre fineness, length, strength, uniformity, yellowness, reflectance, and spinning consistency index.